The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.bodyim.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction from adolescence to young adulthood: Findings from a 10-year longitudinal study

Abstract: Given mixed findings regarding the unique trajectories of female and male adolescents’ body dissatisfaction over time, comprehensive longitudinal examinations are needed. This 10-year longitudinal, population-based study, with 1,902 participants from diverse ethnic/racial and socioeconomic backgrounds in the Minneapolis/St. Paul metropolitan area, examined changes in body dissatisfaction from adolescence to young adulthood. Results revealed that: (a) female and male participants’ body dissatisfaction increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
285
4
36

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(369 citation statements)
references
References 41 publications
22
285
4
36
Order By: Relevance
“…Interestingly, when we analyzed the direction of body dissatisfaction of boys in the accelerated stage, we found they desire to reduce their silhouette (p < 0.001). This finding diverged from previous studies that reported that boys' body dissatisfaction was toward the desire to increase their silhouette in search of a stronger and more muscular profile 20,21 . When analyzing BMI, however, we found that 100% of boys in the accelerated stage were above the 97th percentile (data not shown), which may partially justify the desire to reduce the silhouette.…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly, when we analyzed the direction of body dissatisfaction of boys in the accelerated stage, we found they desire to reduce their silhouette (p < 0.001). This finding diverged from previous studies that reported that boys' body dissatisfaction was toward the desire to increase their silhouette in search of a stronger and more muscular profile 20,21 . When analyzing BMI, however, we found that 100% of boys in the accelerated stage were above the 97th percentile (data not shown), which may partially justify the desire to reduce the silhouette.…”
Section: Discussioncontrasting
confidence: 56%
“…Such a negative body image has led to body dissatisfaction and the percentage of students dissatisfied with their body, regardless of gender, has been on the continuous increase for the past ten years [1,2]. A study in school-age children found that there were more children satisfied with their body weight (39.1%) than those hoping to lose weight (47.1%).…”
Section: Need For Studymentioning
confidence: 99%
“…Due to these changes, the intensity of body dissatisfaction (i.e., the subjective negative evaluation of one's figure or body parts) increases throughout this developmental period (e.g., Bucchianeri, Arikian, Hannan, Eisenberg, & Neumark-Sztainer, 2013). Given that body dissatisfaction is one of the most important risk factors for eating disorders and related health outcomes in adolescence (e.g., NeumarkSztainer, Paxton, Hannan, Haines, & Story, 2006), it is critical to understand factors that contribute to adolescents' body dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%